Health‐Related Quality of Life of People Living with COPD in a Semiurban Area of Western Nepal: A Community-Based Study. (1st July 2021) - Adhikari, Tara Ballav; Rijal, Anupa; Acharya, Pawan; Högman, Marieann; Karki, Arjun; Drews, Arne; Cooper, Brendan G.; Sigsgaard, Torben; Neupane, Dinesh; Kallestrup, Per
Abstract: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of morbidity and mortality in Nepal. It is a progressive lung disease and has a significant impact on the quality of life of patients. Health‐related quality of life (HRQOL) reflects the health‐ and disease‐related facets of quality of life. Limited studies have assessed the impact of COPD on HRQOL and associated factors in Nepal. This study is based on a cross-sectional household survey data from a semiurban area of Western Nepal. A validated Nepali version of St George's Respiratory Questionnaire (SGRQ) was used to measure the HRQOL. COPD was defined together with post-bronchodilator airflow obstruction and the presence of respiratory symptoms. Post-bronchodilator airflow obstruction was defined as Forced Expiratory Volume in 1st second (FEV1 ) to Forced Vital Capacity (FVC) ratio < 0.70. COPD was diagnosed in 122 participants, and their median (IQR) total score of HRQOL was 40 (26 − 69); the score of symptoms, activity, and impact area were 53 (37 − 74), 57 (36 − 86), and 26 (13 − 62), respectively. The overall HRQOL was significantly different in terms of age, occupational status, physical activity, and comorbidities. Disease severity and the presence of respiratory symptoms had a significant difference in HRQOL ( p = 0.0001). Appropriate measures to improve conditions and addressing the associated factors like respiratory symptoms and enhancing physical activity are necessary and important.